The Real-World Utilization Pattern of Increased Utilization of Advanced Topical Adjunctive Hemostats in a Vertically Integrated Healthcare System - Lee Stern; Yi-Chien Lee; Biwen Tao; Lois Lamerato; Gaurav Gangoli; Richard Kocharian; Walter Danker III (Journal of Health Economics and Outcomes Research)
Hemostasis products, such as SURGICEL®, have been increasingly used across a wide variety of surgical procedures to mitigate bleeding-related risks and complications. This retrospective observational study described the utilization pattern of the SURGICEL® family of oxidized regenerated cellulose products (SURGICEL® ORIGINAL, SURGICEL® FIBRILLAR™, SURGICEL SNoW®) in a large, vertically integrated healthcare system, by utilizing electronic medical records (EMR) extracted from August 2013 through June 2015 at Henry Ford Health System (HFHS). Descriptive measurements were compared between SURGICEL® ORIGINAL and advanced SURGICEL® products (SURGICEL® FIBRILLAR™ and SURGICEL SNoW®) for pooled common surgical procedures. Among 1471 patients, 450 received SURGICEL® ORIGINAL, and 1021 received advanced SURGICEL® products. A significantly greater proportion of patients given advanced SURGICEL® products had comorbidities (91.0% vs 85.6%, p=.0024), prior bleeding conditions (49.9% vs 30.9%, p<.0001), and prior use of anticoagulants (27.7% vs 5.3%, p<.0001). Advanced SURGICEL® products were more likely to be used in coronary artery bypass grafting (13.7% vs 1.6%, p<.0001). Among a sub-set of 1420 patients with complete package size information (988 Advanced and 432 ORIGINAL), significantly fewer mean normalized units of Advanced SURGICEL® were used per patient case (3.9 vs 5.5, p<.0001). Despite Advanced SURGICEL® products being utilized in higher risk bleeding situations compared to cases where SURGICEL® ORIGINAL was utilized, fewer overall normalized units of Advanced SURGICEL® were required per patient case. Further research is needed to investigate the implications of topical hemostat use in continuous oozing bleeding situations on outcomes, hospital costs, and resources.